2022
DOI: 10.3389/feart.2022.896634
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Combined Influence of Shield Tunneling and Pile Cutting on Underpinning Piles

Abstract: In this study, the combined influence of shield tunneling and the old pile cutting process on underpinning piles is investigated through finite element method (FEM) modeling based on a shield tunnel project in Nanchang Metro Line 2, China. Numerical models have been developed to analyze the influence of intersection angles and the vertical distance between the underpinning foundation and tunnels on the mechanical responses of underpinning piles during tunnel excavation. Simulation results show that the bending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The 21st century has witnessed significant advancements in underground engineering in China (Ding and Xu, 2017;Liu et al, 2020;Huang et al, 2022). Over the past two decades, numerous tunnels have been successfully constructed (Wang et al, 2022a;Zhou et al, 2022;Wang et al, 2023a). The shield tunneling technology, known for its safety and efficiency, has been extensively utilized in the construction of urban subways and municipal tunnels (Langmaack and Lee, 2016;Xu et al, 2020;Jia and Gao, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The 21st century has witnessed significant advancements in underground engineering in China (Ding and Xu, 2017;Liu et al, 2020;Huang et al, 2022). Over the past two decades, numerous tunnels have been successfully constructed (Wang et al, 2022a;Zhou et al, 2022;Wang et al, 2023a). The shield tunneling technology, known for its safety and efficiency, has been extensively utilized in the construction of urban subways and municipal tunnels (Langmaack and Lee, 2016;Xu et al, 2020;Jia and Gao, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the main part of the project is the way in which to efficiently cut off steel bars. According to incomplete statistics, the reinforced concrete pile foundations or diaphragm walls have been found in more than 20 subway construction projects in more than 10 Chinese cities [7][8][9][10][11]. The pile foundation is the most typical reinforced concrete structure in shield tunneling during the excavating process.…”
Section: Introductionmentioning
confidence: 99%
“…Boonsiri and Zhang et al [7][8][9][10] found that pile groups affect surface movement. Zhang et al 11 proved the feasibility of a pile foundation underpinning construction scheme when a shield tunnel passes through existing piles, studied the comprehensive influence of shield tunnelling and the old pile cutting process on underpinning piles 12 , and proposed a pile foundation underpinning technology for an oblique tunnel crossing a pile group foundation 13 . Wang and Zhao [14][15][16][17] proposed a series of strata reinforcement measures to significantly improve the deformation of existing structures and proposed a new grouting material for the pre-reinforcement of shield tunnels adjacent to existing pile foundations 18 .…”
mentioning
confidence: 99%